2021
DOI: 10.3390/diagnostics11091620
|View full text |Cite
|
Sign up to set email alerts
|

The T2-FLAIR Mismatch Sign as an Imaging Indicator of IDH-Mutant, 1p/19q Non-Codeleted Lower Grade Gliomas: A Systematic Review and Diagnostic Accuracy Meta-Analysis

Abstract: The study’s objective was the evaluation of the diagnostic accuracy of the T2-FLAIR mismatch sign in terms of diagnosing IDH-mutant non-codeleted (IDHmut-Noncodel) lower grade gliomas (LGG) of the brain. We searched the MEDLINE, Scopus and Cochrane Central databases. The last database search was performed on 12 April 2021. Studies that met the following were included: MRI scan assessing the presence of T2-FLAIR mismatch sign, and available IDH mutation and 1p/19q codeletion status. The quality of studies was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, it has a low sensitivity of 42% [ 6 ]. Adamou et al study, showed the diagnostic accuracy for IDH mutant non-codeleted LGGs with specificity and sensitivity of 97% and 40%, respectively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has a low sensitivity of 42% [ 6 ]. Adamou et al study, showed the diagnostic accuracy for IDH mutant non-codeleted LGGs with specificity and sensitivity of 97% and 40%, respectively [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Haralick features derived from the T2WFLAIR sequence can predict the survival of patients with glioblastoma [11]. In addition, a T2WIFLAIR mismatch sign is being investigated, which can indicate the presence or absence of specific mutations [12].…”
Section: Texture-based Featuresmentioning
confidence: 99%
“…However, it occasionally yields false positives in other tumor types and has notable false-negative results. Combining it with additional imaging parameters may enhance its diagnostic accuracy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%